Source Use by Second Year Psychology Students in Online Distance Learning - Nancy Evans Weaver; Estelle Barnard (Flexible Learning Association of New Zealand, 2019)
Previously we used citation analysis on reference lists from beginning psychology students in online distance learning (ODL).  Now we examined second year students' source use.  Sources increased across assignments. Most used were the textbook, instructor and library sources.  The mark achieved increased with number of sources, instructor sources, and library sources.  Instructor and library sources were frequently referenced by both sets of students, and source use related positively to mark.  This research expands the literature by comparing beginning and more advanced students; by replicating results from other researchers; and by examining two assignments from ODL students.